The Influence of the Learning Environment in Student Character Building - Ali Nurdin (Tarbawi, 2020)
This research aims to get information, review and analyze about the influence of learning environment in the formation of student character, research is done using quantitative methods analyzed with descriptive and inference analysis, research is done on teachers in Junior High School (Junior High School) State in Jatisampurna, Bekasi City, West Java. From the results of the study found that there is a positive and significant influence between the family environment on the formation of student character, there is a positive and significant influence between the school environment on the formation of student character, and there is a positive and significant influence between the community environment (social) on the formation of student character. Thus, the improvement of the quality and character of students can be carried out by the implementation of a conducive and quality learning environment. Students who live, get along and interact in a good learning environment will also form good self-quality that will directly affect students in acting and have a good impact in the formation of the character of the student, thus resulting in students of character.